2020
DOI: 10.1371/journal.pone.0232639
|View full text |Cite|
|
Sign up to set email alerts
|

Computed tomography-derived radiomic signature of head and neck squamous cell carcinoma (peri)tumoral tissue for the prediction of locoregional recurrence and distant metastasis after concurrent chemo-radiotherapy

Abstract: Introduction In this study, we investigate the role of radiomics for prediction of overall survival (OS), locoregional recurrence (LRR) and distant metastases (DM) in stage III and IV HNSCC patients treated by chemoradiotherapy. We hypothesize that radiomic analysis of (peri-)tumoral tissue may detect invasion of surrounding tissues indicating a higher chance of locoregional recurrence and distant metastasis. Methods Two comprehensive data sources were used: the Dutch Cancer Society Database (Alp 7072, DESIGN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Introduction of such activation maps into the field of radiomics may provide an addition for clinical interpretability of radiomic models. In the context of peritumoral radiomics for example, where various peritumoral region definitions were reported in different sites ( 46 ), no clear strategy was available to determine the most promising region other than to model and validate each region individually. Therefore the tool presented in this study may guide the user to select the most relevant region in a more efficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of such activation maps into the field of radiomics may provide an addition for clinical interpretability of radiomic models. In the context of peritumoral radiomics for example, where various peritumoral region definitions were reported in different sites ( 46 ), no clear strategy was available to determine the most promising region other than to model and validate each region individually. Therefore the tool presented in this study may guide the user to select the most relevant region in a more efficient way.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Hosney et al [ 31 ] developed a deep learning-based prediction model using a 3D convolutional neuronal network for the prediction of OS for NSCLC patients and observed that the network tended to focus on the interface between the tumour and stroma (parenchyma or pleura) regions in the CT images. In contrast to that, Keek et al [ 32 ] concluded that the consideration of the tumour rim did not lead to an improved prediction of overall survival, loco-regional recurrence and distant metastases in stage III and IV HNSCC patients. However, for the prediction of loco-regional recurrence, a better prediction could be observed for the 5 mm rim-based model compared to the model using the GTV in the exploratory and validation cohort (C-index: 0.86/0.59 and 0.81/0.52, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the detection of metastasis for cervical lymph nodes has become a focus of attention after clinical treatment. In this context, automated detection with the help of ML methods has been conducted with distinct image types recently ( Ariji et al, 2019 ; Dong et al, 2018 ; Keek et al, 2020 ). The nodal status of oral cavity SCC and oropharyngeal SCC is assessed using contrast-enhanced CT scans.…”
Section: Applications Of ML In the Dental Oral And Craniofacial Imaging Fieldmentioning
confidence: 99%